Preventing Hypothermia in Preterm Neonates Using Polyethylene Plastic Bag Wrap: A Systematic Review - Pratiwi, Hikmi Muharromah; Nani, Desiyani; Saryono, Saryono (Universitas Muhammadiyah Semarang, 2024)
Inadequacy of current practices of routine thermal care for heat loss prevention in preterm infants leads to an additional need for immediate hypothermia prevention following delivery and during NICU admission. Plastic bag wrapping has been proven effectively to prevent the hypothermia in preterm infants. A review aimed to investigate the effectiveness of plastic bag wrapping toward hypothermia prevention in preterm infants after birth and during NICU admission. A review was performed by searching of RCT trials using CINAHL, Pubmed, Medline, and EBSCOHost and published in English between January 2013 and August 2023 related to plastic bag or plastic wrap or vinyl bag or polyethylene bag or polyethylene covering, core temperature, and hypothermia. Quasi-experimental studies and randomized controlled trials (RCTs) are included in this study. This study included 10 trials involving 1704 preterm infants: 8 trials reported on poststabilization temperature and incidence of hypothermia, 2 trials showed hypothermia, and one trial in poststabilization temperature for the outcome. Most studies conducted plastic wrap on preterm neonates < 28 weeks of gestational age and for 1-2 hours. Nine studies revealed that plastic bag wrapping was associated with a decline in hypothermia insidences, the higher temperature on baseline and poststabilization temperature compared with routine care or other thermal care. A plastic bag is considered an effective and safe additional intervention for preventing hypothermia in preterm infants less than 28 weeks of gestational age. However, further study could be ensured by performing better-designed studies and a longer follow-up period.